Digital Barricades and Blackouts: A Case of Internet Shutdowns in India - Manisha Madapathi (Media and Communication)
Using internet shutdowns as a reaction to civil unrest has become a common response from the Indian state. In 2022, India remains at the top with the highest number of recorded shutdowns in the world, for the fifth consecutive year. Several state and central governments have used this tactic to suspend the flow of information, either to curtail the ability of citizens to organise through social media networks, dominate discourse around an event, or both. Many such instances have increased the circulation of misinformation, leading to polarised online spaces created partly due to the lack of internet connectivity. Digital disconnection then becomes a condition forced upon its citizens rather than a voluntary choice made by individuals. To explore the impact of internet shutdowns on civic discourse, I look at the case of the farmers’ protest in India, that lasted from September 2020 to November 2021. The movement successfully led to the repeal of the three controversial farm laws. The protest faced challenges due to internet shutdowns along with other forms of crackdown by authorities. I use in-depth interviews to bring in the voices of the various stakeholders who participated in this movement. In this article, I would like to place the farmers’ protest as a vantage point from where one can look at how the Indian state has used internet shutdowns to control dissent.